Responsive polymeric nanoparticles for controlled drug delivery. Issue 12 (20th October 2017) - Neumann, Kevin; Lilienkampf, Annamaria; Bradley, Mark
Abstract: Small‐molecule drugs often have limited solubility, display rapid clearance or poor selectivity that leads to undesired side‐effects. Although prodrug strategies can improve solubility and lower toxicity, activation 'on demand' as well as targeted transport of prodrugs remains a challenge in drug delivery. Responsive polymeric nanoparticles can help meet these challenges with the encapsulation or conjugation of drugs, allowing release at the target site upon triggering by an internal or external stimulus. The adaptable design of polymeric nanoparticles allows them to play a vital role in achieving a specific and desired response following application of a specific stimulus. Here, the most recent progress in responsive polymeric nanoparticles is reviewed with a focus on the chemical properties of the utilized polymers. © 2017 Society of Chemical Industry Abstract : Responsive polymeric nanoparticles have attracted much attention and this review focuses on the broad chemical properties of some of the most exciting and novel polymers that have recently been applied.